Throwing Down the Verbal Gauntlet : The Arabic Invective of Jarīr and al-Farazdaq - Jorgensen, Cory (Middle East and Islamic Studies E-Books Online, Collection 2025., 2025)
Throwing Down the Verbal Gauntlet<.i> showcases Arab "rapper" poets Jarīr and al-Farazdaq. This eighth-century duo is best known for a series of verbal battles (flytings) they carried out over several decades. Verbal Gauntlet argues that these poets performed in order to elevate their own prestige, just as rappers do in modern-day "Dozens" battles. These were performances for performance's sake, a first for a genre traditionally associated with settling tribal disputes. The book provides a new interpretation of this poetry and changes the way we see the intertwining roles of poet, opponent, and audience.